2008
DOI: 10.1590/s0104-56872008000400005
|View full text |Cite
|
Sign up to set email alerts
|

Deglutição em crianças com alterações neurológicas: avaliação clínica e videofluoroscópica

Abstract: Background: swallowing in children with neurologic disorders. Aim: to relate the data obtained in the clinical and in the videofluoroscopic evaluations of swallowing in children with neurologic disorders. Methods: a retrospective analysis of 24 protocols of speech-language evaluation and of medical records of children, of both genders, referred to clinical and videofluoroscopic evaluations of swallowing at the School of Medicine of Ribeirão Preto -University of São Paulo, from January 2001 to June 2005. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
0
11
0
6
Order By: Relevance
“…Este estudo coincide com a literatura (4,6,7,26) , ao verificar que essas avaliações são complementares, sendo essenciais no estudo da disfagia orofaríngea neurogênica.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Este estudo coincide com a literatura (4,6,7,26) , ao verificar que essas avaliações são complementares, sendo essenciais no estudo da disfagia orofaríngea neurogênica.…”
Section: Discussionunclassified
“…A VED consiste em uma nasofibrolaringoscopia tradicional, com o oferecimento de alimentos tingidos com corantes, possibilitando a investigação da fase faríngea da deglutição, a qual apresenta o caminho concomitante entre vias respiratória e digestiva superior (5,6) . Com apoio nos achados da ACF e VED, realizam-se adequações na dieta alimentar da criança com PC, como a escolha de volumes, consistências e manobras compensatórias apropriadas para a alimentação, no intuito de prevenir a ocorrência de manifestações disfágicas (6,7) . Ante o exposto, este estudo tem como objetivo investigar as principais manifestações disfágicas na avaliação clínica e objetiva da deglutição em crianças com PC.…”
unclassified
“…According to Souza and Ferrareto (1998), it is important to consider the possible ways children with CP can be compensated to better coordinate abnormal oral motor skills when swallowing, breathing, and chewing, caused by insufficient selective intrinsic movements dissociated from the tongue and jaw (SOUZA and FERRARETO, 1998). Marrara, Duca, Dantas et al (2008), during a clinical retrospective study on how children with neurological conditions swallow, observed that, in the oral stage, when swallowing liquid or viscous foods, the inadequate presence of food propulsion was most frequently detected as the consequence of an oropharyngeal muscle dysfunction upon chewing, thus interfering with the TMJ's functions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, research results on the clinical aspects of TMDs involve not only pathological articular signs, but also craniofacial, functional, and neurological structural variations, such as head circumference, means of how TMD appear, diet, motor, tonic, and postural involvement (RIES and BERZIN, 2005;ORTEGA, GUIMARÃES, CIAMPONI et al, 2008;PELEGANO, 1976;MARRARA, DUCA, DANTAS et al, 2008;SCHMIDT, BRIESEMEISTER and RIES, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Os problemas alimentares e nutricionais da infância freqüentemente apresentam as disfagias como etiologia principal e estão associados à alteração do desenvolvimento e de saúde 16 . A fundamentação metodológica de avaliação permite que os dados sejam coletados, de maneira pré-estabelecida, possibilitando análise e definição de condutas 17 .…”
Section: Tabela 4 -Avaliação Funcional Da Deglutição Após Intervençãounclassified